(untitled) (Research, Society and Development, 2022)
Cycling is a high performance sport that has characteristics of endurance due to the long distance routes, therefore, adequate eating habits are necessary to enable cyclists to have a good performance. The present study aimed to conduct a field research with data collection and indicators that can bring a reflection on the eating behavior of cyclists and their body composition. A cross-sectional and descriptive study was carried out with a group of cyclists aged between 18 and 60 years, who train with average routes of 150 km for at least twice a week on roads of the DF. The study was carried out in three stages, being the first: application of a questionnaire through Google Forms, addressing food intake and use of supplementation. The second step was the measurement of skinfolds to assess the percentage of total fat, and then the data analysis. Therefore, through the observation of the results it was found that there is a high consumption of ultra-processed foods, and the biggest difficulty reported by cyclists was the lack of time (29.7%), most of them started supplementation through the indication of a nutritionist or doctor (66.7%), however, many still supplement on their own, the body fat percentage of most cyclists is within the appropriate (91.8%). Given this, the research was useful to encourage nutritional monitoring, which is essential for cyclists to use effective strategies to increase performance.